The Transvaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES) Procedures in Contemporary Gynecology: An Appraisal of the Published Evidence and a Review - Mladen Andjić; Zaki Sleiman; Radmila Sparić; Đina Tomašević; Andrea Morciano; Andrea Tinelli (Clinical and Experimental Obstetrics & Gynecology)
Objective: The transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a kind of natural orifice transluminal endoscopic surgery in which the abdominal cavity is reached by using the natural orifices, such as the stomach, rectum, esophagus, and bladder. In comparison to traditional laparoscopic and robotic surgery, there are potential advantages of the vNOTES. This narrative review shows the use of vNOTES in contemporary gynecologic endoscopic surgery. Mechanism: MEDLINE, Scopus, and PubMed searches on these themes were conducted from 1990 to 2023 using a mix of keywords. Papers and articles were identified and included in this narrative review after the authors’ revision and evaluation. Findings in Brief: The vNOTES procedures allow a short surgery time, as well as estimated blood loss and postoperative pain. These procedures are safe and feasible in contemporary endoscopic gynecology surgery. Conclusions: The vNOTES procedures are beneficial for the patients, and to be added to other minimally invasive procedures, such as conventional laparoscopy and robotic surgery. However, further studies about the long-term outcomes of vNOTES procedures are still needed.